2020
DOI: 10.1111/jace.17456
|View full text |Cite
|
Sign up to set email alerts
|

Growth and electrical properties of high‐Curie point rhombohedral Mn‐Pb(In1/2Nb1/2)O3‐Pb(Mg1/3Nb2/3)O3‐PbTiO3 thin films

Abstract: High-quality ternary relaxor ferroelectric (100)-oriented Mn-doped 0.36Pb(In 1/2 Nb 1/2) O 3-0.36Pb(Mg 1/3 Nb 2/3)O 3-0.28PbTiO 3 (Mn-PIMNT) thin films were grown on SrRuO 3-buffered SrTiO 3 single-crystal substrate in a wide deposition temperature range of 550-620°C using the pulsed laser deposition method. The phase structure, ferroelectric, dielectric, piezoelectric properties, and nanoscale domain evolution were studied. Under the deposition temperature of 620°C, the ferroelectric hysteresis loops and curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Because almost no strain has been reported in Aurivillius-type piezoelectric films, we compares the strain performance of the (013)­CBN film with typical Aurivillius-type piezoelectric ceramics as shown in Figure . It can be found that the strain of the (013)­CBN film is much higher than that of other Aurivillius-type piezoelectric ceramics. And its strain is comparable to those of BNT, PMNPT, and KNN based films reported in the literature. Therefore, it provides a piezoelectric film with great potential for the development of high-temperature (>500 °C) piezoelectric MEMS devices.…”
Section: Resultsmentioning
confidence: 61%
“…Because almost no strain has been reported in Aurivillius-type piezoelectric films, we compares the strain performance of the (013)­CBN film with typical Aurivillius-type piezoelectric ceramics as shown in Figure . It can be found that the strain of the (013)­CBN film is much higher than that of other Aurivillius-type piezoelectric ceramics. And its strain is comparable to those of BNT, PMNPT, and KNN based films reported in the literature. Therefore, it provides a piezoelectric film with great potential for the development of high-temperature (>500 °C) piezoelectric MEMS devices.…”
Section: Resultsmentioning
confidence: 61%
“…Due to the influence of substrates, thicknesses, and atomic growth kinetics, PTFs exhibit distinct characteristics compared to its bulk counterpart. Most literature focuses on the relationship between microstructure and properties, with particular emphasis on the link between piezoelectric properties and the compositional characteristics of doping [18][19][20][21], multi-phases [22][23][24][25], etc. In fact, piezoelectric properties mainly originate from piezoelectric response of domain characteristics, such as domain volume fraction, domain size and domain wall/interface density, and mobility [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…No references were found on modeling of the PIP process for CMCs, though experimental studies on this manufacturing process have been reported. Studies on polycarbosilanederived SiC ceramic 25 and SiC/SiC composite 26,27 have shown that porosity decreases and mechanical properties improve with the increasing number of PIP cycles. Zhu et al 28 show that increasing pyrolysis temperature and the concentration of SiC fillers in polycarbosilane polymer result in improved mechanical properties in two-dimensional Carbon/ SiC (C/SiC) composites fabricated using the PIP process.…”
mentioning
confidence: 99%